The expanding GRK interactome: Implications in cardiovascular disease and potential for therapeutic development. (August 2016) - Hullmann, Jonathan; Traynham, Christopher J.; Coleman, Ryan C.; Koch, Walter J.
Graphical abstract: Abstract: Heart failure (HF) is a global epidemic with the highest degree of mortality and morbidity of any disease presently studied. G protein-coupled receptors (GPCRs) are prominent regulators of cardiovascular function. Activated GPCRs are "turned off" by GPCR kinases (GRKs) in a process known as "desensitization". GRKs 2 and 5 are highly expressed in the heart, and known to be upregulated in HF. Over the last 20 years, both GRK2 and GRK5 have been demonstrated to be critical mediators of the molecular alterations that occur in the failing heart. In the present review, we will highlight recent findings that further characterize "non-canonical" GRK signaling observed in HF. Further, we will also present potential therapeutic strategies (i.e. small molecule inhibition, microRNAs, gene therapy) that may have potential in combating the deleterious effects of GRKs in HF.